2010
DOI: 10.1016/j.eururo.2009.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Continence Function following Simulated Birth Trauma Involves Repair of Muscle and Nerves in the Urethra in the Female Mouse

Abstract: Background The natural history and the mechanisms behind the alteration of vaginal distension (VD) in a mouse model are not clear. Objective We examined the temporal sequelae of VD and pudendal nerve transection (PNT) on leak-point pressure (LPP) and the muscular and nerve components of the urethra in mice. Design, setting, and participants Seventy-two virgin female C57BL/6 mice were equally distributed into three groups. The VD group underwent VD for 1 h. The PNT group received bilateral PNT. A control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
0
33
3
Order By: Relevance
“…It was shown that VD decreases leak point pressure (5,17,22) and decreases closure pressure in the middle urethra (17). Histological analyses showed that VD decreases the density of nerve fascicles (5,21) and alters smooth and striated muscle structure (20,36).…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that VD decreases leak point pressure (5,17,22) and decreases closure pressure in the middle urethra (17). Histological analyses showed that VD decreases the density of nerve fascicles (5,21) and alters smooth and striated muscle structure (20,36).…”
Section: Discussionmentioning
confidence: 97%
“…Upon urodynamic evaluation, leak point pressure (LPP) decreases to a nadir level four days following VD and recovers by 20 days. 12 The reversibility of SUI after VD in murine models mimics the clinical scenario of SUI recovery following birth trauma in women.…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, Pan et al [33] found that, compared with sham-treated counterparts, VD-treated virgin rats exhibited significantly lower urethral resistance, as assessed by LPP test, at 10 days but not at 6 weeks after VD. More recently, Lin et al [37] showed that, compared with sham-treated counterparts, VD-treated virgin mice displayed decreased LPP at 4 and 10 days but not at 20 days post-VD. Thus, VD alone is incapable of creating a rodent model suitable for testing SUI treatment efficacy beyond the 6-week time point.…”
Section: Animal Modelsmentioning
confidence: 99%